My side of history - Chin, Peng 1924-2013; Ward, Ian 1938-; Miraflor, Norma O. (Media Masters, 2003)
Chin Peng joined the Communist Party of Malaya (CPM) in January, 1940, as a 15 year-old schoolboy. His commitment to the communist cause, the pre-war anti-colonial struggle against Britain and, eventually, guerrilla warfare against the Japanese invaders saw him propelled rapidly to senior positions within the CPM party structure. By the age of 18 he had become the key link between the communists' Malayan Peoples Anti-Japanese Army (MPAJA) and Britain's clandestine Force 136, then endeavouring to set up intelligence-gathering operations behind enemy lines. While still a teenager he was promoted to head the communist movement's activities in his home state of Perak. Immediately following the Japanese surrender, Chin Peng was appointed to the Central Committee and, ultimately, his party's policy-making Politburo. He was barely 21, At 23, he was formally named the CPM's Secretary General, its highest-ranking figure. By June, 1948, the Malayan Emergency erupted and Chin Peng, four months shy of his 24th year, became the British Empire's most wanted man.